Relationship between post-SARS osteonecrosis and PAI-1 4G/5G gene polymorphisms - Sun, Wei (Eur J Orthop Surg Traumatol, 2013)
OBJECTIVE: To explore the correlation between post-severe acute respiratory symptom (SARS) patients with osteonecrosis, investigate the etiology of post-SARS osteonecrosis and select the sensitive molecular symbols for early diagnosis and distinguish the high-risk population. METHODS: The studied subjects were divided into two groups. Sixty-two post-SARS patients with osteonecrosis were one group, and 52 age- and sex-matched healthy people were as normal controlled group. Empty stomach blood samples from cubital veins were collected from both groups. Plasminogen activator inhibitor (PAI) by means of enzyme-linked immunosorbent assay and PAI-1 4G/5G polymorphism was detected by polymerase chain reaction and solid phase oligonucleotide assay. RESULTS: The blood agents of post-SARS patients changed obviously with 15.64 ± 13.85 U/ml while the control group 7.96 ± 4.27 U/ml; 4G/4G genotype for the PAI-1 polymorphism detected in post-SARS group was more than that of the control group, but had no statistical significance. The plasma PAI activity was related to homozygote 4G/4G genotype. This reveals that homozygote 4G/4G genotype may be a susceptible gene mark to Chinese osteonecrosis patients. CONCLUSION: Plasminogen activator inhibitor-1 is sensitive blood symbol for screening high-risk susceptible population; 4G/4G PAI-1 genotype may be an etiological factor in osteonecrosis.